BEHAVIOR OF THE ANION-RADICALS ELECTROCHEMICALLY GENERATED IN THE REDUCTION OF NOSYL AMIDES - Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Nascimento, O. R.; Koury, E. F. (Elsevier B.V., 1994)
The behaviour of nitrobenzenesulfonamide anion radicals generated from the electrochemical reduction of aliphatic and aromatic amines protected by nitrobenzenesulfonyl (nosyl) groups in N,N-' dimethylformamide has been reported. The species have been characterized by voltammetry and optical and electron spin resonance spectroscopies. The visible spectra of the anion radicals were recorded and the hyperfine splitting constants were assigned to specific proton positions and nitrogen nuclei of the molecule. The stabilities of the anion radicals are affected by electronic properties of the protecting group and specific features of the amines, which show direct influence on the route of cathodic cleavage of the nitrobenzenesulfonamides.
Keywords: NITROBENZENESULFONAMIDE; ANION RADICAL; CATHODIC CLEAVAGE; AMINE DEPROTECTION